2013
DOI: 10.1186/1475-2840-12-12
|View full text |Cite
|
Sign up to set email alerts
|

Coronary aspirate TNFα reflects saphenous vein bypass graft restenosis risk in diabetic patients

Abstract: BackgroundPatients with diabetes mellitus (DM) have an increased risk for periprocedural complications and adverse cardiac events after percutaneous coronary intervention. We addressed the potential for coronary microvascular obstruction and restenosis in patients with and without DM undergoing stenting for saphenous vein bypass graft (SVG) stenosis under protection with a distal occlusion/aspiration device.MethodsSVG plaque volume and composition were analyzed using intravascular ultrasound before stent impla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 52 publications
2
23
0
Order By: Relevance
“…Vein grafts degenerate over time due to the development of large, lipid‐rich, friable plaque comprised of necrotic debris, cholesterol crystals, and often thrombus . Intravascular ultrasound imaging studies have shown that the graft atherosclerosis in patients with diabetes mellitus has more necrotic core with unstable plaques; and after stent implantation there was more particulate debris release when compared to those without diabetes mellitus . Prior surgical literature has shown that recurrent ischemic events and vein graft stenoses were higher among diabetic patients compared with nondiabetics, leading to higher rates of repeat intervention at long‐term follow‐up .…”
Section: Discussionmentioning
confidence: 99%
“…Vein grafts degenerate over time due to the development of large, lipid‐rich, friable plaque comprised of necrotic debris, cholesterol crystals, and often thrombus . Intravascular ultrasound imaging studies have shown that the graft atherosclerosis in patients with diabetes mellitus has more necrotic core with unstable plaques; and after stent implantation there was more particulate debris release when compared to those without diabetes mellitus . Prior surgical literature has shown that recurrent ischemic events and vein graft stenoses were higher among diabetic patients compared with nondiabetics, leading to higher rates of repeat intervention at long‐term follow‐up .…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies and clinical trials have clearly shown that both type I (insulin-dependent) and type II (noninsulin-dependent) diabetics are more prone to developing ischemic heart disease, including acute MI and post-MI complications (Otto et al, 2012;Baars et al, 2013). The diabetic heart is more susceptible to acute myocardial ischemia/reperfusion injury (Alegria et al, 2007;Marso et al, 2007).…”
Section: Diabetesmentioning
confidence: 99%
“…To quantify the effect of coronary arterial and aspirate plasma on RBC aggregation, coronary arterial and aspirate plasma samples of patients (n=3; 40/60 v/v) were added to separated RBCs of healthy volunteers (n=3). We here used plasma from a subgroup of patients with leftover plasma samples from prior studies . Peripheral venous blood was taken from healthy volunteers with the blood group 0 to exclude blood group incompatibilities between the patients’ plasma and the RBCs of the healthy volunteers.…”
Section: Methodsmentioning
confidence: 99%
“…We here used plasma from a subgroup of patients with leftover plasma samples from prior studies. [1][2][3]27 Peripheral venous blood was taken from healthy volunteers with the blood group 0 to exclude blood group incompatibilities between the patients' plasma and the RBCs of the healthy volunteers.…”
Section: (A) Coronary Arterial and Aspirate Plasmamentioning
confidence: 99%